Effects of green credit policy on the risk of stock price crash - Liu, Meng; Dai, Bin; Liu, Yiran (Frontiers in Energy Research, 2023)
Green credit policy (GCP) is a specific instrument for the credit resource allocation dimension in the financial sector, and stock price crashes are an important manifestation of financial market risks that cannot be ignored. However, there are gaps in existing research on how green credit policies affect the stock price crash risk (SPCR). Using the Green Credit Guidelines as a quasi-natural experiment, this paper examines the impact of green credit policies on SPCR of heavily polluting firms. It confirms the crash risk is significantly increased for heavily polluting enterprises, mainly due to facing greater financing pressure; and that corporate governance mechanisms reduce its impact, finding that firms with higher analyst attention, higher levels of independent directors, and higher shares held by institutional investors. The effect between GCP and SPCR is not significant for companies with higher analyst attention, higher levels of independent directors, and higher shareholdings of institutional investors. At the same time, it is less significant in regions with high level of financial development. These results of this paper not only enrich the literature in green credit-related fields, but also provide a reference value for understanding the implementation effect of GCP in China to the stock price crash in the capital market.